Pre-emptive Diclofenac Versus Ketoprofen as a Transdermal Drug Delivery System: How They Face - Jadhav, Pranavi (J Maxillofac Oral Surg, 2017)
AIM: To compare the analgesic efficacy of Diclofenac vis-a-vis Ketoprofen transdermal patch, in the management of immediate post-operative pain following orthognathic procedures. MATERIAL AND METHOD: A prospective, double-blinded, randomised controlled study was conducted among 50 subjects, between 2012 and 2015. These patients were diagnosed clinically and cephalometrically as skeletal and dental class II malocclusion and underwent bi-jaw surgical procedure. In total, 25 Diclofenac and 25 Ketoprofen transdermal patches, sealed in envelopes and numbered, were administered to subjects. The patches used, contained 100 mg of either Diclofenac or Ketoprofen and administered by a nurse prior to induction. Duration of analgesia, severity of pain using Visual Analog Scale, necessity of rescue analgesia (spontaneous pain > 5 on a 10-cm scale) and any other adverse effect associated with the drug were evaluated. RESULTS: Mean duration of analgesia was significantly higher in the Ketoprofen group (20 h), compared to Diclofenac group (13 h) (p = 0.001). Rescue analgesia was required in 12% of subjects who received Diclofenac patch, compared to 4% in Ketoprofen group. None of the subjects showed any allergic reactions. CONCLUSION: The study was designed to evaluate the efficacy of transdermal patch in reduction of post-operative pain in subjects undergoing bi-jaw surgeries. Subjects in both groups were comfortable and returned to early function. However, Ketoprofen transdermal patch had an edge over the Diclofenac transdermal patch with respect to analgesic efficacy.